2016
DOI: 10.1007/s40808-016-0157-z
|View full text |Cite
|
Sign up to set email alerts
|

Isotherm and kinetics modeling of Pb(II) and Cd(II) adsorptive uptake from aqueous solution by chemically modified green algal biomass

Abstract: In this study, the adsorption efficiency of epichlorohydrin modified fresh water green algal biomass was assessed for Pb(II) and Cd(II) uptake from aqueous solution. The process parameters such as contact time, dose, initial metal concentration, solution pH and temperature were optimized. The Langmuir, Freundlich, Temkin and Dubnin-Redushkevich isotherm model was applied to the equilibrium data, which best fitted the Langmuir isotherm indicating homogenous distribution of adsorption sites. The monolayer adsorp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(9 citation statements)
references
References 56 publications
0
9
0
Order By: Relevance
“…Once again, biosorption has appeared to be an efficacious though low-cost solution for the recovery of heavy metals. For the above reasons, sorption on materials of natural origin has become the subject of extensive studies (described, for instance, in [8][9][10][11][12][13][14][15][16][17][18][19][20][21]). The studies have demonstrated that marine algae, which are acquired at a rather low cost, have a considerable sorption capacity.…”
Section: Introductionmentioning
confidence: 99%
“…Once again, biosorption has appeared to be an efficacious though low-cost solution for the recovery of heavy metals. For the above reasons, sorption on materials of natural origin has become the subject of extensive studies (described, for instance, in [8][9][10][11][12][13][14][15][16][17][18][19][20][21]). The studies have demonstrated that marine algae, which are acquired at a rather low cost, have a considerable sorption capacity.…”
Section: Introductionmentioning
confidence: 99%
“…Several techniques available for heavy metals removal from wastewater such as reverse osmosis [1], electrocoagulation [2], ultrafiltration [3], dialysis/electrodialysis [4], and solvent extraction [5] are either costly or less effective due to their own limitations. However, the treatment of aqueous effluents using adsorption of metals onto low cost adsorbents [6][7][8][9][10][11][12] is regarded as an efficient and economical alternative. Biosorption using many agricultural biomass has attracted recent attention because of various functional groups available on the surface of biosorbents for the removal of heavy metals/dyes even at very low concentration from aqueous system [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…The preparation of biological material usually consisted of separating it from mechanical impurities, sometimes rinsing with water and drying into a solid mass in the process of thermal vaporisation of water from, e.g. algae [27], or in the process of lyophilisation [32]. Cleaned and dried samples were stored in paper containers or tightly closed plastic containers [3].…”
Section: Effect Of Samples Preparation and Storage On Their Sorption mentioning
confidence: 99%
“…: Na + , K + , Ca 2+ and Mg 2+ . Also, other authors report the limited heavy metal sorption by cations which are naturally present in the environment [15,27].…”
Section: Effect Of Hydrogen Cations On Sorption Processesmentioning
confidence: 99%
See 1 more Smart Citation